Cerebral lymphoma: clinical radiological correlation. - Spillane, J A (1982)
Twenty patients with primary malignant lymphoma of the brain are described. This tumour tends to involve deep, central structures with subependymal spread and there is a high incidence (30%) of multifocal disease. Many cases present a clinical picture suggesting the location and by inference the possible nature of the tumour: early mental change, somnolence and headache are prominent. In the case of a solitary lymphoma, the computed tomographic appearance is sometimes similar to that of a meningioma whereas, in multifocal disease, confusion with metastases is almost invariable. With CT, it should be possible to reduce the frequency of misdiagnosis, and thus avoid overlooking a potentially radiosensitive lesion.